Evaluation of the Mother Tongue-Based Multilingual Education Program in the Philippines - Abba Joy L. Dagalea; Sharon B. Peralta; Ferdinand T. Abocejo (BIRCU, 2022)
This study is a critical evaluation of the “Mother Tongue-Based Multilingual Education (MTB-MLE)” program implemented in the Philippine primary education level. The MTB-MLE program plays a vital role in the learners’ development process specially in the language acquisition domain. Lending to a content evaluation analysis approach, the study analyzed the strengths and weaknesses of the Program implementation. Findings revealed that the Program implementation within the educational context in the Philippines has brought far reaching beneficial effects like adherence to cultural and linguistic origin while learning and deeper native language comprehension. Meanwhile, the enactment also resulted to some drawbacks as confirmed by the DepEd where the public schools were not yet ready towards the implementation of the MBT-MLE as it requires additional funds concerning to address the inadequacy on instructional and developmental resources. In conclusion, the Program realized valuable effects to the learners, teachers, and within the community context. The authors recommend for a reconfiguration of MTB-MLE strategies and goals to be aligned with the linguistic, economic, and cultural condition. The National Board of Education must engage in language mapping to determine the language distribution in schools where the program is implemented. The local government units can provide vital supports particularly in the provision of operational funds along the implementation of the program.